Impact of Noncoaxial Transcatheter Aortic Valve Implantation on Clinical Outcomes - Domenico Angellotti, MD; Marc Pfluger, MD; Annette Maznyczka, MD, MSc, PhD; Daijiro Tomii, MD; Masaaki Nakase, MD; Stefan Stortecky, MD, MPH; Jonas Lanz, MD; Daryoush Samim, MD; David Reineke, MD; Fabien Praz, MD; Stephan Windecker, MD; Thomas Pilgrim, MD, MSc (JACC: Advances)
Background: Noncoaxial placement of transcatheter heart valves (THVs) relative to the native aortic annulus is occasionally detected on fluoroscopy after transcatheter aortic valve replacement (TAVR). Objectives: This study aimed to evaluate the impact of noncoaxial TAVR deployment on clinical outcomes. Methods: We retrospectively evaluated consecutive patients undergoing transfemoral TAVR in the Bern transcatheter aortic valve implantation registry. Coaxiality between the native annulus and the THV was measured using the 3-cusp view on fluoroscopic images and was defined as the angle between a line intersecting the lower points of native cusps and a line intersecting the lower hinge points of the prosthesis frame. Patients were categorized according to tertiles of coaxiality. Results: Among 2,025 patients (mean age 81.6 ± 6.5 years, mean Society of Thoracic Surgeons Predicted Risk of Mortality 4.2% ± 3.3%) undergoing TAVR with contemporary devices between February 2014 and June 2023, the mean axial angulation of the device relative to the native annulus was 4.1°. According to Valve Academic Research Consortium-3 criteria, patients in the highest tertile of THV axial angle (range, 4.8-21.7°) had reduced device early safety (56.2% vs 82.7%; aHR: 0.67; 95% CI: 0.59-0.76; P < 0.001) and higher rates of stage-2 bioprosthetic valve failure at 1-year follow-up (1.5% vs 0.7%; HR: 3.47; 95% CI: 1.26-9.54; P = 0.016), compared to those with coaxial valve positioning (range, 0.1-3.0). Left ventricle outflow tract calcium volume, predilatation, and valve type were independent predictors of noncoaxial valve implantation. Conclusions: Noncoaxial THV deployment is associated with impaired valve early safety and increased risk of bioprosthetic valve failure 1 year after TAVR.